Idiopathic Intracranial Hypertension in Wales - Strafford, Huw; Miah, Latif; Fonferko-Shadrach, Beata; Hollinghurst, Joe; Rees, Mark I; Sawhney, Inder; Hadjikoutis, Savvas; Powell, Rob; Lacey, Arron; Lacey, Arron (International Journal of Population Data Science, 2020)
Introduction Idiopathic Intracranial Hypertension (IIH) is a condition of unknown aetiology that is strongly associated with obesity. IIH predominantly affects women of childbearing age and causes chronic disabling headaches, visual disturbance and, in a minority of patients, permanent visual loss. Objectives and Approach We characterised the IIH population, epidemiological trends and healthcare outcomes in Wales using routinely collected healthcare data. We used primary and secondary care healthcare diagnosis codes within the Secure Anonymised Information Linkage databank to ascertain IIH cases and controls in a retrospective cohort study between 2003 and 2017. We validated IIH diagnosis codes using anonymised secondary care lists of IIH cases. Results We analysed 35 million patient years of data (2003–2017). There were 1765 cases of IIH in 2017 (85% female). The prevalence and incidence of IIH in 2017 was 76/100,000 and 7.8/100,000/year, a significant increase from 2003 (corresponding figures=12/100,000 and 2.3/100,000/year). The odds ratio for developing IIH in the least deprived quintile compared to the most deprived quintile, adjusted for gender and Body Mass Index (BMI), was 0.65 (95% CI=0.55–0.76). 9% of people with IIH had CSF shunts with less than 0.2% having bariatric surgery. Unscheduled hospital admissions were significantly higher in the IIH cohort compared to controls (rate ratio=5.28, p<0.001) and in the people with IIH with CSF shunts compared to those without (rate ratio=2.02, p<0.01). Conclusion / Implications IIH incidence and prevalence is increasing significantly, corresponding to population increases in BMI, and is associated with increased deprivation. This has important implications for healthcare professionals and policy makers given the comorbidities, complications and increased healthcare utilisation associated with IIH.